Effect of integrated nutrient management on the performance of mature rubber and on soil properties - Philip A; Jessy M.D; Syamala V.K (PLACROSYM XXIII. Climate Resilient Technologies for Sustainability of Plantation Crops, 6-8 March 2019, Central Coffee Research Institute, Chikkamangaluru, Karnataka, India, Abstracts, p. 82.)
A field experiment was initiated at the Central Experiment Station, Chethackal of Rubber Research Institute of India during 2001 to understand the effect of integrating organic manure with fertilizers on the growth and yield of rubber and soil properties. The experimental area was high in organic carbon status. The treatments were farm yard manure (FYM) alone, fertilizer alone, different proportions of fertilizer and FYM and control. Fertilizers and FYM were withdrawn after fourteen years. The treatment 25 per cent RDF + 75 per cent FYM recorded significantly higher girth and mean yield than all other treatments. Mean yield over seven years showed that application of FYM alone resulted in a significantly lower yield than application of fertilizer alone. Increased availability of nutrients viz; P, Ca, Mg, Zn and Mn were observed in FYM applied plots than in fertilizer alone applied plots. Higher microbial population also was noticed in FYM applied plots. The present study revealed that integrating FYM with fertilizer is a better nutrient management option than the practice of applying fertilizer alone in rubber even in soils with high organic carbon status and annual addition of substantial quantity of organic matter through litter recycling.
Keywords: Farm yard manure; Integrated nutrient management; Rubber